CSIG-03. CYCLIC DEPSIPEPTIDE LIGANDS TO TARGET CO-TRANSLATIONAL TRANSLOCATION AND ER PROTEOSTASIS IN GLIOBLASTOMA CELLS. (5th November 2018) - Ishmael, Jane; Wan, Xuemei; Kazemi, Soheila; McPhail, Kerry
Abstract: Coibamide A, is a rare cytotoxic N-methyl-stabilized cyclopeptide originally isolated from a cyanobacterium growing within the marine reserve of Coiba National Park, Panama. We have recently determined that this natural product targets the co-translational translocation machinery and potently inhibits expression of secreted, resident endoplasmic reticulum (ER) and membrane-bound proteins. This mechanism of coibamide A action leads to a pattern of cellular consequences including inhibition of glucose regulated protein 78 (GRP78) expression and a specific pattern of cell stress and death signaling in cultured glioblastoma cells. Exposure to nanomolar concentrations of coibamide A, or the related cyclic depsipeptide natural product apratoxin A, promotes proteasomal degradation of GRP78 and a compensatory upregulation of cytosolic heat shock proteins 40 and 70 that precedes cell death. Co-translational translocation is mediated by the Sec61 translocation channel, which comprises a conserved hetero-oligomeric protein composed of a main pore-forming Sec61alpha subunit plus beta and gamma subunits. Sec61 also signals directly with the protein folding machinery of the ER lumen to maintain proteostasis. The Sec61 translocon channel is not a direct target of any currently approved or experimental drug, however, several natural product structures are now known to target the Sec61 channel and inhibit the co-translational translocation process. Pharmacological inhibitors of Sec61 may be valuable tools to probe GBM biology as SEC61gamma has previously been identified as a proto-oncogene, and Sec61gamma overexpression reported in high versus low grade glioma or normal astrocytes. Natural products have historically been important sources of new chemical structures, particularly for cancer and infectious disease, rather than providing the final drug entity. Although preliminary, the discovery of natural product ligands to target the ER translocation machinery reveals a distinct mechanism to perturb proteostasis in aggressive CNS cancers characterized by high expression of GRP78 and therapeutic resistance.